PENGARUH DIABETES MELLITUS FOOT EXERCISES TERHADAP PERUBAHAN KADAR GULA DARAH PADA PENDERITA DIABETESMELLITUS TIPE II - Dwi Wahyuni, Binarti; Akbar, Amar (JURNAL KEPERAWATAN BINA SEHAT, 2016)
ABSTRACTDiabetic Foot is one of the chronic complications of diabetes most feared. Amputation rate is still high due to diabetes,foot exercises can help blood circulation and strengthen the small muscles of the feet and prevent foot deformity and can lowerblood glucose levels. The purpose of this research was to determine the effect of diabetes mellitus foot exercises to changes in bloodglucose levels in the Village District of Kemlagi Mojodadi Mojokerto. And type of research design used was a pre-experimental(pretest-posttest one group design). In this research there are two variables, the independent variable is Diabetes Mellitus Footexcercises and the dependent variable is the change in blood glucose levels. The population in this research were all patients withDiabetes Mellitus in Mojodadi village in October, amounting to 13 patients with diabetes mellitus with inclusion and exclusioncriteria for the current study there were 8 patients, sampling used was purposive sampling. The results of the analysis by T-test withsignificance level α = 5% and the output of the calculations obtained significance value of 0.001. H0 is rejected if the significance<0.05, so it can be compared to the significant value of 0.001 is less than 0.05, so H0 is rejected, which means that there is aninfluence of diabetes mellitus foot exercises to change blood glucose levels in Mojodadi village Kemlagi district. The decrease inblood glucose levels due to the respondent on the respondent in accordance protab enthusiastic and doing foot exercises becauserespondents want to be cured of diabetes mellitus, and it is also supported by a factor of 46-55 years of age who mostlyKeywords:diabetic foot exercises, diabetes millitus, blood glucose levels